2000
DOI: 10.1108/14635770010314927
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking in local government under a central government agenda

Abstract: Examines the practical experience of benchmarking in the UK local government sector during the period leading to the introduction of an important policy initiative for local government under``New Labour''. Argues that, under conditions of fiscal control, benchmarking has been subsumed under the wider practice of performance measurement in the sector. A critical factor is the primacy of the role of performance monitoring in local government, which in turn results from the controlling nature (in fiscal and polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 4 publications
0
41
0
Order By: Relevance
“…The government has therefore encouraged public-sector organizations to use benchmarking as a useful management tool to achieve best value (Ball et al, 2000). Besides, that, firms are constantly under pressure from external forces such as competition, changing customer needs, government regulation, changing technologies, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The government has therefore encouraged public-sector organizations to use benchmarking as a useful management tool to achieve best value (Ball et al, 2000). Besides, that, firms are constantly under pressure from external forces such as competition, changing customer needs, government regulation, changing technologies, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The Audit Commission's 2 practice of 'compulsory benchmarking' identified in the Bowerman et al (2001, forthcoming) study is effectively a new codification for the Commission's extant practice of publishing local authority performance indicators. It is interesting that against a backdrop of indifference to the results of this exercise, with the exception perhaps of local councillors in relation to poor results (Harbord, 1999), the term 'benchmarking' has permeated the vocabulary of local authority external auditors (see Ball et al, 2000, who discuss how auditors conflate the term 'benchmarking' with moves to establish a new evidence-based database for monitoring local authority performance).…”
Section: How New Management Accounting Slips Into Meeting Old Demandsmentioning
confidence: 97%
“…Some studies (e.g., Ball et al 2000;Ammons 1999) have demonstrated that most UK public organisations tend to focus on league tables as comparators of performance (i.e., data benchmarking), rather than highlighting the causes of differences in performance and generating ideas to improve the processes (i.e., process benchmarking). The NBS is an example of data benchmarking, identifying how performance relates to national benchmarks.…”
Section: Research Contextmentioning
confidence: 98%